A new species of viviparous moth fly (Diptera, Psychodidae, Psychodinae) from the Brazilian Amazon - Cordeiro, Danilo; Bravo, Freddy (Biota Neotropica, 2008)
A new species of Psychoda Latreille from Brazil is described and illustrated, and represents the first record of viviparous species in the genus Psychoda.